The Study of Employee Engagement and Positive Outlook WRT Work-From-Home - Mrinali Tikare, Latha Sreeram, Samruddhi Verlekar (Mathematical Statistician and Engineering Applications, 2022)
— It is now an established fact that our whole world is reeling under the effects of this great pandemic of COVID -19 which in turn has automatically affected almost each and every organization in their bid to survive and grow. In these unforeseen scenarios, many organizations have been forced to adopt ‘work-from-home’ as the new normal to keep up their businesses floating. However, keeping employees engaged when they are busy working remotely has become a preliminary and vital issue. The present study aims to measure the employee engagement level and their outlook while working from home. The data has been collected from 287 white collar employees by using Stratified Sampling technique from Mumbai by circulating google questionnaire during May – June 2020. The researchers selected only young educated population falling between 20 to 40 age group. After exhaustive literature review the study opted validated scales namely; the Utrecht Work Engagement Scale (UWES: Schaufeli et al. (2002)) and the E-Work Life Scale (EWL: Grant et al., 2013] with some justified item modification and performed Reliability Analysis and Principal Component Analysis. Descriptive statistical techniques were used to determine the engagement level of the employees. Additionally, Inferential statistics performed by using Pearson’s Correlation technique for testing the hypotheses. The findings of the study revealed that there was a moderate, positive and significant correlation among Outlook for Work from Home (O-WFH) and Vigour, Dedication and Absorption. The Multiple Regression Model confirmed that Dedication and Absorption are making a statistically significant unique contribution to the prediction of the positive Outlook for Work from Home. The rationale of the results was discussed thereafter in the light of earlier literature. The study concluded that Dedication and Absorption will increase the positive outlook of the white-collar employees while working from home. The findings of the study have theoretical as well as practical implications for all stakeholders engaged in almost all diverse businesses across the world in this new normal scenario.